Exploring the key deteriorative microorganisms on ancient ivories unearthed from the Sanxingdui Ruins site during temporary cold storage - Lao, Guangjie; Zhou, Zhiwei; Wu, Rao; Wang, Chong; Wu, Wei; Lv, Shan; Liu, Jiancheng; Xie, Zhenbin; Dinnyés, András; Yuan, Haibing; Tan, Xuemei; Sun, Qun (Frontiers in Microbiology, 2024)
The ancient ivories unearthed from the Sanxingdui Ruins site are valuable cultural relics, however, the microbial biodeterioration on ivories during temporary cold storage poses a great threat to their later long-term preservation. Here, the combination of high-throughput sequencing and biochemical assays was applied for the in-depth investigation of the key deteriorative microorganisms colonizing on the ivories and the tracing of their origin, as well as the assessment of the ethanol disinfection impact on the microbial communities on ivories. It was observed that the surfaces of ivories were scattered by the fungal patches of white, dark grey, and hedge green colors during cold storage. The high-throughput sequencing results showed that the genera Mortierella (38.51%), Ilyonectria (14.43%), Penicillium (1.15%), and Aspergillus (1.09%) were the dominant fungi, while Pseudomonas (22.63%), Sphingopyxis (3.06%), and Perlucidibaca (2.92%) were the dominant bacteria on ivories. The isolated Aspergillus A-2 resulted in the highest amount of calcium releasing from the degradation of hydroxyapatite (HAP), the main component of ivory, by the organic acids produced, including oxalic acid and citric acid. The fast expectation-maximization for microbial source tracking (FEAST) analysis revealed that the majority of the fungi (57.45%) and bacteria (71.84%) colonizing on the ivories were derived from the soils surrounding ivories in the sacrifice pits, indicating soils as the primary source for the spoilage microbes growing on ivories. The dominant strains could degrade cellulose, the key components of wet cotton towels commonly applied on ivories for moisture maintenance, aiding the spoilage microbes colonizing on ivories. Notably, the ivory disinfection with 75% ethanol during the cleansing significantly decreased the relative abundance of the dominant genera of Ilyonectria, Aspergillus, and Pseudomonas, with Mortierella becoming the dominant one on ivories. Together, the fungi, particularly Aspergillus and Penicillium, played a significant role in the microbial biodeterioration of unearthed ancient ivories by producing the organic acids. These results may improve the control of the microbial biodeterioration and develop more efficient strategies for the longtime conservation of unearthed ancient ivories and other cultural relics.